(untitled) (Sains Humanika, 2012)
Emotional intelligence is one of important aspect in enhancing the effectiveness of the work, creativity, ability to communicate, display technical ability, emotional self-control, and pressure to succeed in one’s career employees in the organization. Thus indirectly, emotional intelligence employees are able to influence the effectiveness of an organization. That is why it is essential that employees have high emotional intelligence. This study was conducted to identify the level and the dominant dimensions of emotional intelligence among customs officials W17 grade at Royal Malaysian Customs Department Johor Bahru. A total of 210 customs officers grades W17 selected for the study. This study is a survey that uses instruments that have been developed by Bar On. This Instrument has five dimensions of intrapersonal, interpersonal, stress management, ability to adapt and mood. Results showed that the level of emotional intelligence of customs officials W17 grade is at a moderate level. The results also showed that the general mood is the most dominant dimension of emotional intelligence, while the least dominant is adaptability dimension.